To transform the equation −2y=14−6x to slope-intercept form, we need to solve for y.
Step 1: Distribute -2 to the terms inside the parentheses on the right side of the equation.
-2y = 14 - 6x
Step 2: Move the constant term to the right side of the equation.
-2y + 6x = 14
Step 3: Divide both sides of the equation by -2 to solve for y.
y = -3x + 7
So, the equation −2y=14−6x can be written in slope-intercept form as y = -3x + 7.
Transform the linear equation −2y=14−6x to slope-intercept form.(1 point)
y=
6 answers
no
Apologies for the incorrect response earlier. Let me correct the transformation of the equation.
To transform the equation −2y = 14 - 6x to slope-intercept form, we need to solve for y.
Step 1: Move the constant term to the right side of the equation by adding 2y to both sides.
-2y + 2y = 2y + 14 - 6x
0 = 14 - 6x + 2y
Step 2: Rearrange the terms on the right side.
2y = -6x + 14
Step 3: Divide both sides of the equation by 2 to solve for y.
y = (-6/2)x + 14/2
y = -3x + 7
So, the equation −2y=14−6x can be written in slope-intercept form as y = -3x + 7.
To transform the equation −2y = 14 - 6x to slope-intercept form, we need to solve for y.
Step 1: Move the constant term to the right side of the equation by adding 2y to both sides.
-2y + 2y = 2y + 14 - 6x
0 = 14 - 6x + 2y
Step 2: Rearrange the terms on the right side.
2y = -6x + 14
Step 3: Divide both sides of the equation by 2 to solve for y.
y = (-6/2)x + 14/2
y = -3x + 7
So, the equation −2y=14−6x can be written in slope-intercept form as y = -3x + 7.
no.
Apologies for the mistake. Let's try again.
To transform the equation −2y = 14 - 6x to slope-intercept form, we need to solve for y.
Step 1: Divide both sides of the equation by -2 to isolate y.
y = (14 - 6x)/(-2)
Step 2: Simplify the right side of the equation.
y = -7 + 3x
So, the equation −2y = 14 - 6x can be written in slope-intercept form as y = 3x - 7.
To transform the equation −2y = 14 - 6x to slope-intercept form, we need to solve for y.
Step 1: Divide both sides of the equation by -2 to isolate y.
y = (14 - 6x)/(-2)
Step 2: Simplify the right side of the equation.
y = -7 + 3x
So, the equation −2y = 14 - 6x can be written in slope-intercept form as y = 3x - 7.
no